Inactivation of Prefrontal Cortex Delays Emergence From Sevoflurane Anesthesia - Huels, Emma R.; Groenhout, Trent; Fields, Christopher W.; Liu, Tiecheng; Mashour, George A.; Pal, Dinesh (Frontiers in Systems Neuroscience, 2021)
Studies aimed at investigating brain regions involved in arousal state control have been traditionally limited to subcortical structures. In the current study, we tested the hypothesis that inactivation of prefrontal cortex, but not two subregions within parietal cortex—somatosensory barrel field and medial/lateral parietal association area—would suppress arousal, as measured by an increase in anesthetic sensitivity. Male and female Sprague Dawley rats were surgically prepared for recording electroencephalogram and bilateral infusion into prefrontal cortex (N = 13), somatosensory barrel field (N = 10), or medial/lateral parietal association area (N = 9). After at least 10 days of post-surgical recovery, 154 µM tetrodotoxin or saline was microinjected into one of the cortical sites. Ninety minutes after injection, rats were anesthetized with 2.5% sevoflurane and the time to loss of righting reflex, a surrogate for loss of consciousness, was measured. Sevoflurane was stopped after 45 minutes and the time to return of righting reflex, a surrogate for return of consciousness, was measured. Tetrodotoxin-mediated inactivation of all three cortical sites decreased (p < 0.05) the time to loss of righting reflex. By contrast, only inactivation of prefrontal cortex, but not somatosensory barrel field or medial/lateral parietal association area, increased (p < 0.001) the time to return of righting reflex. Burst suppression ratio was not altered following inactivation of any of the cortical sites, suggesting that there was no global effect due to pharmacologic lesions. These findings demonstrate that prefrontal cortex plays a causal role in emergence from anesthesia and behavioral arousal.